Effects of Anodal Transcranial Direct Current Stimulation (atDCS) on Sentence Comprehension. (29th January 2019) - Lum, Jarrad A. G.; Clark, Gillian M.; Rogers, Caitlyn M.; Skalkos, James D.; Fuelscher, Ian; Hyde, Christian; Enticott, Peter G.
Abstract: Objectives: This study examined the effects of anodal transcranial direct current stimulation (a-tDCS) on sentence and word comprehension in healthy adults.Methods: Healthy adult participants, aged between 19 and 30 years, received either a-tDCS over the left inferior frontal gyrus ( n =18) or sham stimulation ( n =18). Participants completed sentence comprehension and word comprehension tasks before and during stimulation. Accuracy and reaction times (RTs) were recorded as participants completed both tasks.Results: a-tDCS was found to significantly decrease RT on the sentence comprehension task compared to baseline. There was no change in RT following sham stimulation. a-tDCS was not found to have a significant effect on accuracy. Also, a-tDCS did not affect accuracy or RTs on the word comprehension task.Conclusions: The study provides evidence that non-invasive anodal electrical stimulation can modulate sentence comprehension in healthy adults, at least compared to their baseline performance. ( JINS, 2019, 25, 331–335)